2006
DOI: 10.1080/00103620500449336
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine and Metolachlor Sorption to Switchgrass Residues

Abstract: Herbicide retention by residue mulch in vegetative filter strips could be an effective attenuation mechanism for removing herbicides from runoff. Adsorption studies were conducted to quantify the amount of atrazine and metolachlor that can be adsorbed and removed from runoff by thatch or fresh switchgrass residue. Adsorption of C 14 -atrazine and metolachlor on thatch or fresh switchgrass residue was conducted by using concentrations of 2.5, 7.5, 13.2, and 26.4 mmol L 21 and a 24-h equilibration period. Adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…These reductions were attributed to slower runoff velocities and increase in soil retention. Mersie et al (2006) reported significant levels of sorption of atrazine and metachlor to switchgrass residues that accumulate over time on filter strips. Entry and Watrud (1998) tested the ability of Alamo switchgrass to remediate soil contaminated by cesium-137 and strontium-90.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…These reductions were attributed to slower runoff velocities and increase in soil retention. Mersie et al (2006) reported significant levels of sorption of atrazine and metachlor to switchgrass residues that accumulate over time on filter strips. Entry and Watrud (1998) tested the ability of Alamo switchgrass to remediate soil contaminated by cesium-137 and strontium-90.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Growing perennial grasses such as switchgrass and prairie cordgrass for biofuel in riparian zones, stream waterway buffers, and highly erodible cropland areas has been proposed and investigated (Dominguez-Faus et al, 2009;Mersie et al, 2006;Powers et al, 2010;Sanderson, 2008;Sanderson et al, 2001;Tufekcioglu et al, 2003;Koh et al, 2009; http://nac.unl.edu/buffers/guidelines/4 opportunities/6.html; http://www.globalbioenergy.org/uploads/ media/0702 FAO -Water quality and environmental dimensions in biofuel production.pdf; https://bioenergy.ornl.gov/papers/ misc/switgrs.html). Cultivating perennial grass in these high reliefs, intensive agriculture areas can improve local environment conditions and ecosystem services (Dominguez-Faus et al, 2009;Powers et al, 2010;Sanderson et al, 2001;Tufekcioglu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…When retained by the crop residue, herbicide losses are likely to occur due to photo degradation, volatilization, and its adsorption by plant residues. The adsorption by plant residues is dependent on their degree of decomposition and age (Mersie et al, 2006). Studies with metolachlor have reported its possible retention by plant residues and thus reduced efficacy (Oliveira et al, 2001;Teasdale et al, 2003;Fontes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%